Plasma protein-based identification of neuroimage-driven subtypes in mild cognitive impairment via protein-protein interaction aware explainable graph propagational network - Park, Sunghong; Kim, Doyoon; Lee, Heirim; Hong, Chang Hyung; Son, Sang Joon; Roh, Hyun Woong; Kim, Dokyoon; Nam, Yonghyun; Lee, Dong gi; Shin, Hyunjung; Woo, Hyun Goo (Computers in Biology and Medicine, 2024)
As an early indicator of dementia, mild cognitive impairment (MCI) requires specialized treatment according to its subtypes for the effective prevention and management of dementia progression. Based on the neuropathological characteristics, MCI can be classified into Alzheimer's disease (AD)-related cognitive impairment (ADCI) and subcortical vascular cognitive impairment (SVCI), being more likely to progress to AD and subcortical vascular dementia (SVD), respectively. For identifying MCI subtypes, plasma protein biomarkers are recently seen as promising tools due to their minimal invasiveness and cost-effectiveness in diagnostic procedures. Furthermore, the application of machine learning (ML) has led the preciseness in the biomarker discovery and the resulting diagnostics. Nevertheless, previous ML-based studies often fail to consider interactions between proteins, which are essential in complex neurodegenerative disorders such as MCI and dementia. Although protein-protein interactions (PPIs) have been employed in network models, these models frequently do not fully capture the diverse properties of PPIs due to their local awareness. This limitation increases the likelihood of overlooking critical components and amplifying the impact of noisy interactions. In this study, we introduce a new graph-based ML model for classifying MCI subtypes, called eXplainable Graph Propagational Network (XGPN). The proposed method extracts the globally interactive effects between proteins by propagating the independent effect of plasma proteins on the PPI network, and thereby, MCI subtypes are predicted by estimation of the risk effect of each protein. Moreover, the process of model training and the outcome of subtype classification are fully explainable due to the simplicity and transparency of XGPN's architecture. The experimental results indicated that the interactive effect between proteins significantly contributed to the distinct differences between MCI subtype groups, resulting in an enhanced classification performance with an average improvement of 10.0 % compared to existing methods, also identifying key biomarkers and their impact on ADCI and SVCI.
Keywords: Alzheimers disease; Cognitive impairment; Graph neural networks; Interactive effect; Machine-learning; Mild cognitive impairment; Plasma protein; Plasma protein biomarker; Protein-protein interactions; Vascular dementia; Aged; Alzheimer Disease; Biomarkers; Blood Proteins; Cognitive Dysfunction; Female; Humans; Machine Learning; Male; Neuroimaging; Protein Interaction Maps; Alzheimer's disease; Graph neural network; Mild cognitive impairment; Plasma protein biomarker; Protein-protein interaction; Vascular dementia